2017
DOI: 10.1021/acs.nanolett.7b02896
|View full text |Cite
|
Sign up to set email alerts
|

From Nonluminescent Cs4PbX6 (X = Cl, Br, I) Nanocrystals to Highly Luminescent CsPbX3 Nanocrystals: Water-Triggered Transformation through a CsX-Stripping Mechanism

Abstract: We report a novel CsX-stripping mechanism that enables the efficient chemical transformation of nonluminescent CsPbX (X = Cl, Br, I) nanocrystals (NCs) to highly luminescent CsPbX NCs. During the transformation, CsPbX NCs dispersed in a nonpolar solvent are converted into CsPbX NCs by stripping CsX through an interfacial reaction with water in a different phase. This process takes advantage of the high solubility of CsX in water as well as the ionic nature and high ion diffusion property of CsPbX NCs, and prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

21
395
3
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 387 publications
(422 citation statements)
references
References 31 publications
21
395
3
3
Order By: Relevance
“…The cesium lead halide perovskite of Cs 4 PbBr 6 is a typical zero-dimensional (0D) inorganic MHP, in which the octahedra are completely isolated by cation bridges and charge carriers are localized within the ordered metal halide component 710 . The electronic structure and optical properties of these materials are expected to show a significant dependence on pressure 1116 .…”
Section: Introductionmentioning
confidence: 99%
“…The cesium lead halide perovskite of Cs 4 PbBr 6 is a typical zero-dimensional (0D) inorganic MHP, in which the octahedra are completely isolated by cation bridges and charge carriers are localized within the ordered metal halide component 710 . The electronic structure and optical properties of these materials are expected to show a significant dependence on pressure 1116 .…”
Section: Introductionmentioning
confidence: 99%
“…16 The proposed origin of the green PL is either intrinsic to Cs 4 PbBr 6 (due to the presence of defects) 11,12,14,1726 or from contamination by CsPbBr 3 NC-like impurities. 13,2742 …”
mentioning
confidence: 99%
“…13,27 This can be done via the insertion of PbBr 2 , the extraction of CsBr with water or with Prussian Blue, or the extraction of Pb 2+ with amines. 13,27,28,33,37 Several groups have reported that the size and shape of the starting Cs 4 PbBr 6 NCs can be used to tune the size of the final CsPbBr 3 NCs (Figure 5b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…First discovered in 2014, LHP NCs are of great interest because the bright, narrow-band photoluminescence (PL) of this new class of nanomaterials can be readily tuned from ultraviolet to near-infrared wavelengths simply by tailoring either the halide composition or size of NCs. [27][28][29][30][31][32][33] An otable advantage of LHP NCs over conventional semiconductor NCs (such as CdSe and InP) is their defect tolerance (i.e., the apparently benign nature of structural defects with respect to optical and electronic properties). [34][35][36] Great effort has been devoted to synthesizing various LHP NCs,investigating their photophysical properties,a nd exploiting them for use in optoelectronic or photovoltaic devices.…”
Section: Introductionmentioning
confidence: 99%